Unveiling the therapeutic potential of caudatin: Structural optimization, pharmacological mechanisms, and therapeutic implications - Shi, Guohui; Ni, Linlin; Kong, Xiaoni; Ren, Rutong; Shi, Xinyu; Xu, Yang; Qu, Zhizi; Zhou, Honglei; Zhang, Xiusheng (Frontiers in Pharmacology, 2025)
Caudatin is a C21 steroidal glycoside isolated from many species of the genus Cynanchum, has been utilized by traditional medicine to treat cancer and inflammation which is increasingly being considered a drug candidate because of the pharmacological activity it displays. This review provides a discussion of caudatin’s structure-activity relationship (SAR), pharmacology, and therapeutic uses along with a synthesis of future challenges. Caudatin is a potent anti-cancer therapeutic that has been shown to modulate several important signaling pathways, which include but are not limited to: Wnt/β-catenin, NF-κB, and PI3K/AKT pathway, induce apoptosis through ROS mediated mitochondrial dysfunction, reduce metastatic spread through inhibition of epithelial-mesenchymal transition (EMT), and have an anti-inflammatory effect through inhibition of JNK/AP-1/NF-κB signaling. Caudatin has also displayed neuroprotection in models of Alzheimer’s disease by activating TFEB and the autophagosome-lysosomal pathway mechanism of action, while also modulating PPARα. Furthermore, pharmacokinetic studies indicate that caudatin is rapidly absorbed and is able to selectively tail hepatic tissue while having little to no toxicity or significant adverse events in pre- clinical animal studies. Structure-activity studies suggest that modifications on the C-3 hydroxyl position, primarily with nitrogen heterocycles and/or sugars greatly enhance the bioactivity and solubility. With caudatin being such a great scaffold for medicinal chemistry, there is great opportunity to take advantage of caudatin as a building block to generate novel therapies which bridge traditional medicine with modern drug discovery. The future is aimed primarily at a combination strategy of synthetic derivatives, translational studies, and formulations. In further exploring caudatin as a treatment for cancer and neurodegenerative diseases, and inflammation.